ISLAMOPHOBIA : ANTI-MUSLIM SENTIMENT AND ITS IMPACT ON MUSLIM WOMEN - Ade Salamah (Ikatan Dosen Menulis, 2023)
In contemporary times Islamophobia became a global sociological concern - not just for Indonesia; but for the entire Muslim world. Internationally Western mainstream media, started referencing Islam, Islamic countries and muslim demographics as “terrorist”, “extremists”, and as only “radicals”. The 9/11 incident in New York marked the hight of Islamophobia internationally. In some countries, like France, Britain and the US, where the majority of the population is non-Muslim, this anti-Muslim sentiment can be seen in several forms, such as Muslims being treated disrespectfully and unfairly. These anti-muslim manifestations certainly has a very devastating impact on particularly Muslim women living in non-Muslim (Western) countries, especially for those wearing the hijab and burqa. Indonesia, which internationally has the greatest Muslim majority, is not immune to the unjust phenomenon of Islamophobia, with several schools and institutions prohibiting students from wearing, for example the hijab. The purpose of this study is to realize a religious life marked by the values of mutual respect, inclusivity and tolerance without discrimination. The method used in this study is qualitative, while the data collection technique uses the library research method. Limitations and formulations of the problems to be problematised are as follows: 1) the forms and causes of Islamophobia in Indonesia and Western countries; and 2) how Islamophobia impacts particularly Muslim women living in non-Muslim countries. The final aims of this study are: 1) provide understanding and/or greater clarity about Islam; and 2) protecting the rights of women, especially Muslim women, so that they can practice their beliefs freely, without any prejudice and discrimination.